Association between obstructive sleep apnea and erectile dysfunction: a systematic review and meta-analysis. Issue 3 (June 2018) - Kellesarian, S.; Malignaggi, V.; Feng, C.; Javed, F.
Abstract The purpose of the present systematic review and meta-analysis was to assess the association between obstructive sleep apnea (OSA) and erectile dysfunction (ED). To address the focused question, "Is there an association between OSA and ED?" indexed databases were searched up to May 2017 without time or language restrictions using various key words including: obstructive sleep apnea, sleep apnea syndromes, erectile dysfunction, sleep-disordered breathing, snoring, sexual function, and impotence. Review articles, case-reports and case-series, commentaries, letters to the editor, interviews and updates, studies assessing the efficacy of OSA treatment in the improvement of ED, or studies evaluating the efficacy of ED treatment in the improvement of OSA were excluded. Twenty-eight observational studies were included for qualitative synthesis. Overall, 19 studies had a cross-sectional design, 7 studies were case–control, and 2 were cohort studies. The odds ratios (OR) with a 95% confidence interval were calculated from 10 studies. The combined OR was 0.45, with a 95% confidence interval of 0.18–0.71, indicating that in patients without OSA, the risk of ED is significantly lower compared with patients with OSA. The available evidence shows that OSA is associated with a higher risk of ED; however, further well-designed controlled clinical trials and longitudinal prospective studies are needed in this regard.